POLITENESS STRATEGIES PERFORMED BY TEACHERS TO EFFECTIVELY ASSIST CHILDREN WITH AUTISM IN THEIR LEARNING PROCESS - Sugini Sugini; Djatmika Djatmika; Maryadi Maryadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
The paper discusses the politeness strategies conducted by teachers of autism centre in Surakarta in supporting them doing their jobs effectively. They are professionals who care and treat children with autism for their cognitive as well as psychomotoric development. Data were collected from four learning processes performed by four different female teachers with a different child for each. The analysis was carried out to see how politeness strategies selected by the teachers help them in performing effective assisting and learning process for the kids. The results show that politeness strategies were conducted by the teachers in two modes—verbally and non-verbally. They were exploited to accommodate the skill transfer to the children with autism effectively. The autism condition of each child governed each teacher to select the types of the politeness—in which bald on strategy dominated the exploitation, followed by positive and negative politeness. In addition, no teacher chose off record strategy for her class. This exploitation is considered effective due to the exceptional condition of the children. Clear and direct utterances which encourage their self esteem are good choice for them. Such utterances in that features can be accommodated by those three types of politeness strategies in either verbal or non-verbal mode.